2020
DOI: 10.3389/fmicb.2020.00334
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of NDM-5-Producing Escherichia coli in a Teaching Hospital in Chongqing, China: IncF-Type Plasmids May Contribute to the Prevalence of blaNDM–5

Abstract: The newly emerging NDM-5 confers increased antibiotic resistance and attracts extensive global attention, but the prevalence, dissemination mechanism, and clinical significance of NDM-5 among clinical Escherichia coli (E. coli) infections have not been thoroughly characterized to date. In the present study, 109 unique carbapenemresistant E. coli (CR-EC) isolates were collected in Southwest China, from 2013 to 2017, among which 41 (37.61%) CR-EC isolates were identified as NDM-5-producers, with most isolates ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 26 publications
6
16
1
Order By: Relevance
“…1a ). A similar structure has been found on an IncFIA/FIB plasmid (pNDM-5-1001) of an E. coli ST410 clinical isolate from China ( 12 ) and on an IncFII plasmid (pNDM-5-IT) of an E. coli ST167 clinical isolate from Italy ( 13 ), although there is a difference in the direction of the mphA - mrx - mphR module. Two copies of bla OXA-48 , both located between two copies of insA - insB (IS 1R ), were present on the chromosome of FUJ80155 ( Fig.…”
Section: Observationsupporting
confidence: 64%
“…1a ). A similar structure has been found on an IncFIA/FIB plasmid (pNDM-5-1001) of an E. coli ST410 clinical isolate from China ( 12 ) and on an IncFII plasmid (pNDM-5-IT) of an E. coli ST167 clinical isolate from Italy ( 13 ), although there is a difference in the direction of the mphA - mrx - mphR module. Two copies of bla OXA-48 , both located between two copies of insA - insB (IS 1R ), were present on the chromosome of FUJ80155 ( Fig.…”
Section: Observationsupporting
confidence: 64%
“…IncF type plasmids have also been shown to contribute to the dissemination of bla NDM-5 among E. coli [17,18,46]. In this study, we observed that the bla NDM-5 in E. coli from neonates was carried on IncFIA type plasmids.…”
Section: Discussionsupporting
confidence: 49%
“…The bla NDM-5 from these isolates co-existed with bla CTX-M-15 , bla TEM-1B and bla OXA-1 located on the IncFIA plasmid. Other recent studies in Africa and elsewhere have observed co-harbouring of bla NDM-5 and bla CTX-15 , bla TEM-1B , bla OXA-1 in the same plasmid type in E. coli [3,12,46]. Co-localization of bla NDM-5 and extended spectrum β-lactamase (bla CTX-M-15 ) plus other resistance genes in the same plasmid could increase the dissemination of multiple resistances in a single gene transfer event.…”
Section: Discussionmentioning
confidence: 91%
“…Our results found that AR_N1_I is highly homologous to bla NDM– 1 surrounding fragments encoded by Enterobacter cloacae174 chromosome, indicating that bla NDM– 1 surrounding fragments could transfer between the IncX3 plasmid and Enterobacter chromosome. In 2020, Zou et al (2020) reported that the genetic environment containing bla NDM– 5 could be divided into five subtypes. Among them, Type A corresponds to the AR_N5_I genetic environment in our study.…”
Section: Discussionmentioning
confidence: 99%